2023
DOI: 10.1038/s41598-023-36062-y
|View full text |Cite
|
Sign up to set email alerts
|

Wearable-based accelerometer activity profile as digital biomarker of inflammation, biological age, and mortality using hierarchical clustering analysis in NHANES 2011–2014

Abstract: Repeated disruptions in circadian rhythms are associated with implications for health outcomes and longevity. The utilization of wearable devices in quantifying circadian rhythm to elucidate its connection to longevity, through continuously collected data remains largely unstudied. In this work, we investigate a data-driven segmentation of the 24-h accelerometer activity profiles from wearables as a novel digital biomarker for longevity in 7,297 U.S. adults from the 2011–2014 National Health and Nutrition Exam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Our results revealed that the influence of circadian acrophase on biological aging was more pronounced in younger individuals, suggesting a plausible link between circadian misalignment or disruption and the adverse health implications associated with the aging process. This aligns with recent research, which has shown that young adults with circadian disturbance were seemingly healthy with no comorbid conditions but in fact, exhibited elevated inflammation and accelerated biological aging 18 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results revealed that the influence of circadian acrophase on biological aging was more pronounced in younger individuals, suggesting a plausible link between circadian misalignment or disruption and the adverse health implications associated with the aging process. This aligns with recent research, which has shown that young adults with circadian disturbance were seemingly healthy with no comorbid conditions but in fact, exhibited elevated inflammation and accelerated biological aging 18 .…”
Section: Discussionsupporting
confidence: 91%
“…Studies consistently show that prolonged and repeated circadian disruption ultimately increases mortality risk and shortens longevity 16 . More recent work unveils that disrupted CR is additionally associated with decreased healthspan and advanced biological aging as estimated through blood biomarkers, underscoring the significant role of CR in healthy longevity as well as overall lifespan 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data quality metrics provided by the UKB accelerometer working group, we excluded n=19,079 participants with unreliable accelerometry data if any of the following conditions were met: flagged by the UKB as having data problem; insufficient wear time (<72 h of wear time or no wear data in each 1h period of the 24-hour cycle); unreliable or not well-calibrated data; and accelerometry data with a nonzero count of interrupted recording periods 30 . We further excluded participants with missing in any of the 5-minute epochs per day to ensure the continuous time series of accelerometry data over the course of 24-hours 18 .…”
Section: Data Processing Of Wearable-derived Accelerometer Activity Datamentioning
confidence: 99%
“…Studies consistently show that prolonged and repeated circadian disruption ultimately increases mortality risk and shortens longevity [14][15][16] . More recent work unveils that disrupted CR is additionally associated with decreased healthspan and advanced biological aging as estimated through blood biomarkers, underscoring the significant role of CR in healthy longevity as well as overall lifespan 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…7 For instance in primary prevention, wearable-device-measured physical activity profiles are associated with systemic inflammation, biological age, and all-cause mortality. 26 …”
Section: Introductionmentioning
confidence: 99%